Isolation and screening of phytase-producing fungi for phytase production by solid state fermentation using agro wastes - Afolabi, Folake; Atunwa, Samuel (Journal of BioScience and Biotechnology, 2025)
Phytases are phosphatase enzymes that catalyze the hydrolysis of phytic acid and its salts. This study aimed to isolate and screen for phytase-producing fungi from cereals, fruits, palm kernel cake and soil samples by solid state fermentation. Isolation and identification was done using standard methods. The fungal isolates were screened for phytase production using phytase screening medium (PSM) agar. The isolates with the highest and consistent zone of hydrolysis were used. Eighty-seven (87) fungal isolates were obtained while eighteen showed consistent zone of hydrolysis. These were screened to five (5) isolates: Aspergillus niger PKruw7, Aspergillus awamori Pkruw5, Aspergillus flavus PBDJ7, Aspergillus niger MOJ5b and Penicillium chrysogenum OBDJ1.They were used for solid state fermentation using rice bran, soy bean and wheat bran for phytase production. The optimized conditions for phytase production were: 40ºC temperature, 5.5 pH, 1% w/w fructose and 0.5% w/w yeast extract by both Aspergillus niger PKruw7 and Aspergillus flavus PBDJ7, 40ºC, 4.5 pH, 1% w/w fructose and 0.5% w/w NH4NO3: Aspergillus awamori Pkruw5, 25ºC, 6.5 pH, 1% w/w fructose and 0.5% w/w NH4NO3: Aspergillus niger MOJ5b and 40ºC, 4.5 pH, 1% w/w sucrose and 0.5% w/w (NH4) 2SO4: Penicillium chrysogenum OBDJ1with incubation period of 120 hours optimal for all the isolates. Maximum phytase production from optimized culture conditions include; incubation period of 5 days, temperature of 40°C, pH of 4.5 to 6.5, fructose (1% w/w), yeast extract and ammonium nitrate (0.5% w/w). Phytase can be applied in animal feed to enhance digestibility and nutrient availability.